ISLAMIC EDUCATION OF CHILDREN Raising Children in Islam-How to raise children into responsible Muslim adults? - Yuliawati, Fitrah (Universitas Islam Madura, 2016)
Parents hold enormous leverage in terms of what they teach their children and accordingly how their children grow up as adults. Islam, therefore, hold parents responsible for steering their children’s upbringing according to the guidelines of the Quran and the Prophet’s (SallallahuAlaihiWaSallam) traditions. The Prophet (s) said: “Allah (SWT) will ask every caretaker about the people under his care, and the man will be asked about the people of his household” (Nasa’i, Abu Da’ud).Children have the right, therefore, to be raised as responsible Muslim adults and parents must ensure that right appropriately. Parents must be conscious and take an active role in guiding their children and families on the path of truth. The Prophet Muhammad (s) said: “Every one of your (people) is responsible, and everyone is responsible for whatever falls under his responsibility. A man is like a shepherd of his own family, and he is responsible for them” (Bukhari and Muslim).